EXPLORING INDONESIAN RELIGIOUS TOLERANCE AND ORIENTATIONAL PLURALISM THROUGH BARASUARA’S "HAGIA" - Anadza, Hirshi; Rommel Utungga Pasopati; Syarifuddin (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2023)
This study aims to provide a comprehensive understanding of how Barasuara's Hagia manifests religious tolerance and orientational pluralism in Indonesia. It is important to highlight that the responsibility for religious tolerance and pluralism extends beyond leadership to every stratum of society. By leveraging music as a vehicle to promote pluralism and instill values within individuals at their core, this approach may prove to be more effective than other governmental-implemented formalized methods. Religion can impact the behavior of young people, who are more ardent than older people, who are more cautious. By applying a qualitative approach, this study shows how orientational pluralism in the Hagia of Barasuara exemplifies religious tolerance. Through the emphasis on divergent viewpoints and other interconnected themes, the lyrical compositions of Hagia demonstrate the potential for religious tolerance and are therefore indicative of a pluralistic and diverse ethos. In conclusion, the lyrical composition suggests that pluralistic understanding can improve inclusive views toward one's own and other religions. Hagia's recognition and admiration of various religious beliefs demonstrate that sheer relativism is insufficient; individuals must show proactive compassion for others.